Prediction and correlation of computed tomography findings with first clinical presentation in patients diagnosed primary brain tumour - Abdullah, Mohd Shafie (2001)
Prediction and correlation of cotnputed tomography findings with first clinical presentations in patients diagnosed primary brain tumour. The brain twnour is increasing in incidence nowadays probably with presence of new high technoloy facilities such as computed tomography, magnetic resonance imaging and angiogarphy. There is a wide spectrum of presentation of patients in term age and clinical presentations. An early detection of the twnours will give a good outcome currently with the availability of neurosurgeons and neuroimaging facilities. Neuroimaging play an important role in detecting the lesion, hence to reduce tile morbidity and mortality.